The Relevance of Leisure Noise to Hearing Threshold Shifts: A Longitudinal Analysis Among Adolescents - Walser-Reichenbach, Sandra M.; Gerstner, Doris G.; Twardella, Dorothee; Jenkac, Christina; Weilnhammer, Veronika; Hendrowarsito, Lana; Perez-Alvarez, Carmelo; Steffens, Thomas; Stilianakis, Nikolaos; Herr, Caroline E.W.; Heinze, Stefanie (Journal of Speech Language and Hearing Research, 2022)
PURPOSE: The aim of this study was to analyze the association of total leisure noise exposure and hearing threshold shifts over 5 years among adolescents enrolled in the Ohrkan cohort study. METHOD: The Ohrkan cohort of 2,148 students aged 13-19 years was recruited from 2009 to 2011 and followed up 5 years later. Complete baseline and follow-up reports on exposure and outcome were available for 989 participants. Leisure noise exposure was assessed by questionnaires, and clinical audiometric examinations were performed. Two outcomes were defined: occurrence of the Niskar notch pattern and audiometry showing maximum hearing threshold values at 3, 4, and 6 kHz (both ears). Longitudinal analysis using generalized estimating equations was performed. RESULTS: High total leisure noise exposure, defined as an energy equivalent of a 40-hr week of > 85 dBA, was estimated for 32.7% of students at baseline and 63.8% at follow-up. A noise notch was observed in 1.1% of adolescents at baseline and 3.3% at follow-up. At baseline, the maximum measured threshold shift was 55 dB, which increased to 85 dB at the follow-up. Longitudinal analysis did not reveal an association between leisure noise exposure and hearing thresholds. Hearing threshold shifts or noise notches were associated with sex, school type, and time point of measurement. CONCLUSIONS: No relationship was found between leisure noise and hearing thresholds. Male adolescents and those attending secondary general schools, with graduation following completion of ninth or 10th grade, had a greater likelihood of developing hearing threshold shifts. Prevention programs should focus on these risk groups. SUPPLEMENTAL MATERIAL: https://doi.org/10.23641/asha.19233462.
CRIS-Team Scopus Importer:2022-03-18